Don't blame it on WTO law: an analysis of the alleged WTO law incompatibility of destination based taxes - Pirlot, A (University of Florida Press, 2020)
The idea that corporations should be taxed in the jurisdiction where they make their sales or provide their services is getting more and more attention in the policy debate on international taxation. In 2016, U.S. House Speaker Paul Ryan proposed to introduce a destination-based cash flow tax (DBCFT) in order to reform the United States’ corporate income tax (CIT). Moreover, in the last few years, more and more countries have considered the adoption of new rules to tax the digital economy in the country where the users and/or the consumers are located.